2016
DOI: 10.1016/j.ijdevneu.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of synaptic development in the hippocampus of diabetic Goto‐Kakizaki rats

Abstract: Insulin receptor signaling has been shown to regulate essential aspects of CNS function such as synaptic plasticity and neuronal survival. To elucidate its roles during CNS development in vivo, we examined the synaptic and cognitive development of the spontaneously diabetic Goto-Kakizaki (GK) rats in the present study. GK rats are non-obese models of type 2 diabetes established by selective inbreeding of Wistar rats based on impaired glucose tolerance. Though they start exhibiting only moderate hyperglycemia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Under observation with a high-powered microscope, SAP102 was intensely expressed in the cytoplasms throughout the process areas but not in the nuclei (Figs 1-4). The fluorescence intensities of SAP102 in the hippocampal subfields CA1, CA3 and DG increased gradually with age from P0 to P56; in adulthood, SAP102 maintained relatively higher levels from P56 to P8 m. In aged rats (P20 m), SAP102 unexpectedly displayed no significant decrease in the CA1 and DG regions (P > 0.05) but did decrease in the CA3 subregion (P < 0.05, P20 m vs. P8 m), which contrasted with the results of previous studies (Sans et al 2000;Matsunaga et al 2016).…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Under observation with a high-powered microscope, SAP102 was intensely expressed in the cytoplasms throughout the process areas but not in the nuclei (Figs 1-4). The fluorescence intensities of SAP102 in the hippocampal subfields CA1, CA3 and DG increased gradually with age from P0 to P56; in adulthood, SAP102 maintained relatively higher levels from P56 to P8 m. In aged rats (P20 m), SAP102 unexpectedly displayed no significant decrease in the CA1 and DG regions (P > 0.05) but did decrease in the CA3 subregion (P < 0.05, P20 m vs. P8 m), which contrasted with the results of previous studies (Sans et al 2000;Matsunaga et al 2016).…”
Section: Resultscontrasting
confidence: 71%
“…Our data herein showed that SAP102 was highly expressed in the rat hippocampus from P56 to P8 m and displayed no significant decreases in the CA1 and DG regions at P20 m. Numerous reports have demonstrated that SAP102 is expressed in the hippocampus at young ages and is then mostly replaced by PSD95 in later stages of life (Sans et al 2000;Elias et al 2006;Murata & Constantine-Paton, 2013). Matsunaga reported that the SAP102 level in the Wistar rat hippocampus increased from P35 to P5 m (Matsunaga et al 2016), which is unlike the reduced level of SAP102 expression from P35 to P6 m found by Sans et al (2000). In humans, researchers examined SAP102 expression in the brain tissues of humans aged 57-87 years, finding that SAP102 maintained relatively higher expression levels in the inferior temporal lobe, occipital lobe and hippocampus (Proctor et al 2010).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Other assays may be more sensitive and could detect changes at earlier timepoints. However, previous studies in GK rats only revealed deficits at later times, including deficits in novel object recognition observed at 24 weeks of age, 48 deficits in memory retention observed at 10 weeks, 49 and deficits in olfactory memory at 6 to 10 months. 35…”
Section: Discussion Retinal Changes Appear Prior To Cognitive and Motmentioning
confidence: 70%
“…Indeed, early changes in insulin receptor signaling in the hippocampus were shown to inhibit synaptic maturation and potentially cause cognitive deficits in the GK rat. 49 In addition, decreased inhibition from amacrine cells has been proposed to increase rod bipolar cell signaling in the diabetic retina, 51 suggesting that amacrine cells could be investigated in the GK rat as a target for synaptic change during hyperglycemia in retinal development. Contrary to our results, other groups have reported reduced ERG amplitudes in the GK rat.…”
Section: Supernormal Erg Amplitudes In the Gk Ratmentioning
confidence: 99%